2010
DOI: 10.3109/09638288.2010.488711
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the elderly after vision loss

Abstract: Purpose. To assess the degree of participation of the visually impaired elderly and to make a comparison with populationbased reference data. Method. This cross-sectional study included visually impaired elderly persons (55 years; n ¼ 173) who were referred to a low-vision rehabilitation centre. Based on the International Classification of Functioning, Disability and Health (ICF) participation in: (1) domestic life, (2) interpersonal interactions and relationships, (3) major life areas, and (4) community, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 52 publications
4
83
1
4
Order By: Relevance
“…Many studies showed that during the developmental stage of children and adolescents with visual impairment, they continue becoming more vulnerable to life circumstances [9]. Low vision is associated with negative consequences such as limitations in day-to-day activities [10,11], poor physical function [10], depressive symptoms [12][13][14][15][16], and low quality of life [17]. There is an internal relationship between sensory impairment, mental and social functioning, and communication [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that during the developmental stage of children and adolescents with visual impairment, they continue becoming more vulnerable to life circumstances [9]. Low vision is associated with negative consequences such as limitations in day-to-day activities [10,11], poor physical function [10], depressive symptoms [12][13][14][15][16], and low quality of life [17]. There is an internal relationship between sensory impairment, mental and social functioning, and communication [18].…”
Section: Introductionmentioning
confidence: 99%
“…3 Eerder onderzoek toonde aan dat visueel beperkten beperkingen ervaren bij participatie in het dagelijks leven. 4 Daarnaast ervaren zij psychosociale problemen, 5 en gevoelens van sociale isolatie 6 en eenzaamheid. 7 Eenzaamheid is een negatieve situatie, gekenmerkt door een gemis aan (kwaliteit van) bepaalde relaties en resulteert in verminderd welbevinden.…”
Section: Inleidingunclassified
“…Study participants originated from a previous crosssectional study [14] that included visually impaired persons who were aged ≥ 55 years, able to speak Dutch, able to understand instructions concerning response sets and referred to a lowvision rehabilita tion centre according to the Dutch guidelines [32]. According to these guidelines, persons with a visual acuity ≤ 0.5 Snellen who have problems in daily life due to the visual impairment should be referred for rehabilitation as well as persons with a visual field <30 degrees.…”
Section: Study Participantsmentioning
confidence: 99%
“…Previous research showed that vision loss has a profound impact on daily functioning [4][5][6] and quality of life [7][8][9][10], as indicated by an impaired functional ability and psychological distress [11][12][13]. In addition, visually impaired elderly persons per ceive restrictions in participation [14,15] and participate less in household activities, sports activities and recreational activities as compared to peers [14].…”
Section: Introductionmentioning
confidence: 99%